Renal Allograft Loss Caused by Cardiorenal Syndrome. Issue 6 (June 2015) - Waiser, Johannes; Knebel, Fabian; Rudolph, Birgit; Wu, Kaiyin; Müller, Eda; Sanad, Wasiem; Budde, Klemens; Neumayer, Hans-Hellmut; Halleck, Fabian
<x xml:space="preserve">Abstract</x> Background Scientific interest in cardiorenal syndrome (CRS) affecting the native kidneys is increasing. In contrast, no relevant literature exists on CRS after kidney transplantation. Methods Prompted by the clinical course of a renal allograft recipient, who lost his graft because of CRS, we systematically investigated the frequency, the clinical appearance, the underlying cardiac pathophysiology, and the renal pathology of patients with graft loss caused by CRS between 2006 and 2011 at our center. Results We identified seven cases of graft loss caused by CRS, six cases of CRS type II, and one case of CRS type I. The proportion of death-censored graft losses caused by CRS was 4.6% (7/152 patients). Median graft survival after diagnosis was 6 (1–62) months. Clinically, all patients suffered from repeated episodes of decreasing renal function together with severe volume overload necessitating multiple hospitalizations (range, 23–308 days) and ultrafiltration treatments (range, 4–45). Cardiac investigation revealed a combination of left heart failure, right heart failure and moderate-to-severe tricuspid regurgitation in 5/6 CRS type II patients. Renal allograft pathology showed the same pattern of tubular injury in all biopsy specimens: microvesicular tubular epithelial cytoplasmatic vacuolization and luminal dilatation with flattening of the epithelium. Conclusion We propose that the diagnosis of CRS after renal transplantation should be based on the following triad: (i) otherwise unexplained decrease of renal function together with severe volume overload; (ii) functionally relevant heart disease, predominantly left heart failure in combination with right heart failure, and tricuspid regurgitation; and (iii) a typical histopathologic pattern of tubular injury.